Do selective immunisation against tuberculosis and hepatitis B reach the targeted populations? A nationwide register-based study evaluating the recommendations in the Norwegian Childhood Immunisation Programme. Issue 17 (12th April 2016) - Feiring, Berit; Laake, Ida; Molden, Tor; Håberg, Siri E.; Nøkleby, Hanne; Seterelv, Siri Schøyen; Magnus, Per; Trogstad, Lill
Highlights: Target groups had lower coverage of target vaccines than of other programme vaccines. The coverage of the target vaccines varied according to parental country of birth. Universal programme vaccine coverage was similar in target and non-target groups. Abstract: Background: Selective immunisation is an alternative to universal vaccination if children at increased risk of disease can be identified. Within the Norwegian Childhood Immunisation Programme, BCG vaccine against tuberculosis and vaccine against hepatitis B virus (HBV) are offered only to children with parents from countries with high burden of the respective disease. We wanted to study whether this selective immunisation policy reaches the targeted groups. Methods: The study population was identified through the Norwegian Central Population Registry and consisted of all children born in Norway 2007–2010 and residing in Norway until their second birthday, in total 240, 484 children. Information on vaccinations from the Norwegian Immunisation Registry, and on parental country of birth from Statistics Norway, was linked to the population registry by personal identifiers. The coverage of BCG and HBV vaccine was compared with the coverage of vaccines in the universal programme. Results: Among the study population, 16.1% and 15.9% belonged to the target groups for BCG and HBV vaccine, respectively. Among children in the BCG target group the BCG vaccine coverage was lower than the coverage of pertussis and measles vaccine (83.6% vs. 98.6% and 92.3%, respectively). Likewise, the HBV vaccine coverage was lower than the coverage of pertussis and measles vaccine in the HBV target group (90.0% vs. 98.6% and 92.3%, respectively). The coverage of the targeted vaccines was highest among children with parents from South Asia and Sub-Saharan Africa. The coverage of vaccines in the universal programme was similar in targeted and non-targeted groups. Conclusions: Children targeted by selective vaccination had lower coverage of the target vaccines than of vaccines in the universal programme, indicating that selective vaccination is challenging. Improved routines for identifying eligible children and delivering the target vaccines are needed. Universal vaccination of all children with these vaccines could be considered.